A Climatological Study of Successive Tropical Cyclone Events in North Atlantic - Xia Sun; Lian Xie (Atmosphere, 2022)
This study presents the climatological characteristics and key environmental features that are conducive to the development of successive tropical cyclone events (STCs) over the North Atlantic Ocean. Composite analyses were conducted to analyze the temporal, spatial, and mean characteristics of the environmental conditions associated with historical STC events during the study period of 1950–2020. The results show that the tropical cyclone (TC)-induced Rossby waves could explain a majority of Atlantic STCs when newly formed TCs develop to the east of the pre-existing TC during the study period. The remaining STCs which could not be explained by the Rossby wave dispersion theory were likely the result of favorable environmental conditions conducive to the occurrence of the successive development of TCs. The composite analysis of the environmental conditions at various time scales reveals that the low-frequency variability of the environmental conditions likely plays a significant role in modulating the STCs over the North Atlantic Ocean.